Model Desain Tata Ruang Kawasan Kampung Batik Celaket Berbasis Kawasan Produktif di Kota Malang - Lalu Mulyadi; Lalu Achmad Juniarta Dias Eka Wahyudi (Unika Soegijapranata Semarang, 2020)
Malang city is one leading city in tourism field that embodied concept of Tribina Cita Kota Malang where part of it is to make Malang as tourism city. Aside as a tourist destination, Malang also grows as service, trade and industrial city. By these enormous economic and trade abilities will be able to change the orientation from a tourism city into a shopping tourism city. Kampung Batik Celaket area is increasingly recognized in public eye by many physical and non physical improvements also icons creation inside Kampung Batik Celaket environment. There are five factors as design reference: factors of location, environtmental athmosphere, outdoor layout, road circulation system, and facade of buildings. These factors will be arranged into good construction in order to give comfort and safety in its shopping athmosphere.To begin with, these factors must undergo a research to understand their characteristics, so the result study can be used as a reference for planning and designing area of Kampung Batik Celaket to be one ideal, feasible and productive village.This study conducted directly on site which began from surveys, interviews, and extraction important elements through visual studies.Then, the obtainable data are tested for formulating reccommendations of designs from each subregion.